THE INFLUENCE OF REWARD AND PUNISHMENT ON THE LEARNING INTEREST OF 5TH GRADE STUDENTS IN TEGALTIRTO - Mulyantoro, Praja; Khosiyono, Banun Haifah Cahyo (Department of Primary education, Faculty of Teacher Training and Education, Universitas Su, 2023)
This research aims to (1) determine the influence of rewards and punishments on learning interest, (2) determine the influence of rewards on learning interest, and (3) determine the influence of punishments on learning interest. This research uses a quantitative approach through an ex post facto technique. The total 5th grade students of SD Negeri in Tegaltirto Kapanewon Berbah District of Sleman Regency constitute the research population of 116 students, and the research sample consists of 90 students. The research sample is determined through simple random sampling using the Slovin formula. The data collection method involves a psychological scale pilot-tested on 50 students. In this case, the research instrument was validated through expert judgment via content validity. Meanwhile, reliability was calculated using Cronbach’s alpha formula, with an R-value of 0.7, and item discrimination was calculated using the product-moment correlation formula. The research findings indicate that (1) the provision of rewards and punishments affects learning interest with a contribution of 44.2%; (2) rewards influence students’ learning interest with a contribution of 34.23%; (3) punishments influence students’ learning interest with a contribution of 9.97%; and (4) the regression equation is Y = 29.974 + 0.528X1 + 0.226X2.